Analysis of Critical Thinking Skills Tests on Local Issues of Viral Infections in Food and Horticultural Crops Using the Rasch Model - Handayani, Sri; Suranto, Suranto; Fatmawati, Umi; Havyarimana, Célestin (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
In the 21st century, students must have critical thinking skills to face increasingly complex problems and challenges. Students' critical thinking skills need to be measured with test questions. This research is a quantitative and qualitative descriptive study to analyze critical thinking skills questions including validity, reliability, difficulty level, and differentiating power. The research instrument was in the form of descriptive questions tested on 32 students. Data analysis used the Rasch model assisted by Winstep 3.73 software. The results of the validity of the question items showed that 83.33% of the questions were valid and the instrument reliability was good. The difficulty level of the questions meets the criteria of very easy, easy, difficult, and very difficult but the distribution is uneven. The differentiating power of the test items was obtained by three groups, which means good. The conclusion is that the test instrument is suitable as a tool for evaluating critical thinking skills regarding viral infections in food and horticultural crops. Analisis Tes Ketrampilan Berpikir Kritis terhadap Isu Lokal Infeksi Virus pada Tanaman Pangan dan Hortikultura Menggunakan Model Rasch ABSTRAK: Pada abad 21, siswa harus memiliki keterampilan berpikir kritis untuk menghadapi permasalahan dan tantangan yang semakin kompleks. Keterampilan berpikir kritis siswa perlu diukur dengan soal-soal tes. Penelitian ini merupakan penelitian deskriptif kuantitatif dan kualitatif untuk menganalisis soal-soal keterampilan berpikir kritis meliputi validitas, reliabilitas, tingkat kesukaran, dan daya pembeda. Instrumen penelitian berupa soal uraian yang diujikan kepada 32 orang siswa. Analisis data menggunakan model Rasch dengan bantuan software Winstep 3.73. Hasil validitas butir soal menunjukkan 83,33% soal valid dan reliabilitas instrumen baik. Tingkat kesukaran soal memenuhi kriteria sangat mudah, mudah, sukar, dan sangat sukar tetapi sebarannya tidak merata. Daya pembeda butir soal diperoleh tiga kelompok yang berarti baik. Kesimpulannya adalah instrumen soal layak digunakan sebagai alat untuk menilai keterampilan berpikir kritis tentang infeksi virus pada tanaman pangan dan hortikultura.